The lost Van Gogh : a novel - Santlofer, Jonathan, 1946- (Sourcebooks Landmark, 2024)
"For years, there have been whispers that, before his death, Van Gogh completed a final self-portrait. Curators and art historians have savored this rumor, hoping it could illuminate some of the troubled artist's many secrets, but even they have to concede that the missing painting is likely lost forever. But when Luke Perrone, artist and great-grandson of the man who stole the Mona Lisa, and Alexis Verde, daughter of a notorious art thief, discover what may be the missing portrait, they are drawn into a most epic art puzzles. When only days later the painting disappears again, they are reunited with INTERPOL agent John Washington Smith in a dangerous and deadly search that will not only expose secrets of the artist's last days but draws them into one of history's darkest eras. Beneath the paint and canvas, beneath the beauty and the legend, the artwork has become linked with something evil, something that continues to flourish on the dark web and on the shadiest corridors of the underground art world."--